(untitled) (Central Medical College Journal, 2024)
Background: Zinc is an important trace element and a potent antioxidant. Its deficiency causes a common comorbidity with numerous chronic diseases including hypertension and diabetes mellitus, associated with development and progression of various complications. Objective: The present study has been undertaken to evaluate the effects of zinc supplementation on blood pressure in type 2 diabetic patients. Methods: This prospective interventional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka between January 2016 to December 2016. In this study, a total number of 46 diagnosed type 2 diabetic patients of both sexes were selected with age ranging from 40 to 55 years. Among them, 26 type 2 diabetic patients with supplementation of oral zinc (40mg/day) for 12 weeks were considered as study group (Group B). Another 25 age matched type 2 diabetic patients without supplementation of oral zinc were considered as control group (Group A) for comparison. All subjects were selected from Outpatient Department of Endocrinology, Dhaka Medical College Hospital, Dhaka on the basis of inclusion and exclusion criteria. Their blood pressure (BP) was measured and serum zinc level was estimated by Spectrophotometric method accordingly. These parameters were studied 2 times in all subjects of control and study groups i.e. at the beginning of study (base line) and after 12 weeks of study period. Data were collected in pre-designed structured questionnaire form by the researcher herself. For statistical analysis, paired Student’s ‘t’ test and unpaired Student’s ‘t’ test were performed as applicable using SPSS for windows version 22.0. Results: In this study, after zinc supplementation resulted in a significant (p<0.001) decrease in both systolic and diastolic blood pressure in study group but there was no significant change observed in control group. Conclusions: After analyzing the results of the study, it can be concluded that oral zinc supplementation can be useful for improving blood pressure in type 2 diabetic patients. Central Medical College Journal Vol 7 No 1 January 2023 Page: 41-46